1981
DOI: 10.1152/ajpendo.1981.240.3.e245
|View full text |Cite
|
Sign up to set email alerts
|

Effects of amino acids on membrane potential and 86Rb+ fluxes in pancreatic beta-cells

Abstract: The membrane potential of beta-cells was studied with microelectrodes in mouse islets and their potassium permeability was evaluated by measuring 86Rb+ fluxes in rat islets. In the absence of glucose, L-leucine, its metabolite ketoisocaproate, and its nonmetabolized analogue 2-aminonorbornane-2-carboxylic acid (BCH) depolarized beta-cells and triggered bursts of electrical activity like glucose. The effect of leucine was weak, but was potentiated by a low concentration of glucose or by theophylline; the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
77
0
2

Year Published

1987
1987
2004
2004

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 25 publications
12
77
0
2
Order By: Relevance
“…Recent detailed studies using leucine, arginine, lysine and alanine have demonstrated three basic mechanisms which appear to underlie the effects of amino acids on insulin release (Hellman et al 1971;Henquin & Meissner, 1981Charles & Henquin, 1983;Henquin, 1987). Leucine is transported into the p-cells where it is efficiently metabolized, giving rise to qualitatively similar changes in membrane potential and ionic fluxes as described for glucose.…”
Section: Amino Acidsmentioning
confidence: 98%
See 4 more Smart Citations
“…Recent detailed studies using leucine, arginine, lysine and alanine have demonstrated three basic mechanisms which appear to underlie the effects of amino acids on insulin release (Hellman et al 1971;Henquin & Meissner, 1981Charles & Henquin, 1983;Henquin, 1987). Leucine is transported into the p-cells where it is efficiently metabolized, giving rise to qualitatively similar changes in membrane potential and ionic fluxes as described for glucose.…”
Section: Amino Acidsmentioning
confidence: 98%
“…Whereas glucose and other nutrients (e.g. certain amino acids) are thought to stimulate insulin secretion primarily by increasing cytoplasmic Ca2+ (Henquin, 1987), neural and hormonal entero-insular stimuli appear to amplify insulin secretion through direct intracellular activation of adenylate cyclase or phospholipase C (Hellman, 1986;Turk et al 1987).…”
Section: I N D a M M O R G A N A N D O T H E R S Action Of N U T mentioning
confidence: 99%
See 3 more Smart Citations